The Cancellation of a Plaintiff's Lawsuit Due to Bad Faith in Mediation (A Study of Decision Number: 103/Pdt.G/2023/PN Tjk - Rusli, Tami; Ramadhan, Suta; Devira, Devira (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
A lawsuit is often dismissed if the plaintiff is proven to have acted in poor faith during the legal process. This is crucial for maintaining the integrity of the Indonesian judicial system, particularly in the context of resolving civil disputes involving consumers. Mediation, as a dispute resolution method, is crucial for resolving disputes involving unlawful acts in consumer financing agreements. However, its success depends heavily on the good faith of the parties involved. If one party lacks good faith, mediation will be ineffective. The research question is how to resolve disputes regarding the dismissal of a plaintiff's lawsuit who lacks good faith in mediation based on Decision Number 103/Pdt.G/2023/PN Tjk? And what are the judge's considerations regarding the dismissal of a plaintiff's lawsuit who lacks good faith in mediation based on Decision Number 103/Pdt.G/2023/PN Tjk?The research method uses two approaches: a normative juridical approach and an empirical approach. Data collection was conducted through literature review and fieldwork. Data analysis was conducted qualitatively. There was one source in this research: a Judge at the Tanjung Karang District Court. The settlement of the dispute over the cancellation of the plaintiff's lawsuit for failing to act in good faith during mediation complies with the dispute resolution procedures under Law of the Republic of Indonesia Number 8 of 1999 concerning Consumer Protection (UUPK), which was carried out by PT. Astra Sedaya Finance. The Unlawful Act (PMH) for the Violation of the Inclusion of Standard Clauses committed by PT. Astra Sedaya Finance has seriously harmed the Plaintiff, and the Plaintiff deserves legal certainty at the Tanjung Karang District Court. The Judge adjudicated by declaring the Plaintiff's failure to act in good faith during the mediation process, declaring the Plaintiff's lawsuit inadmissible, ordering the Plaintiff to pay mediation costs of IDR 800,000.00 (eight hundred thousand rupiah), and ordering the Plaintiff to pay court costs, which to date have been set at IDR 676,000.00 (six hundred seventy-six thousand rupiah). The judge's considerations regarding the dismissal of the plaintiff's lawsuit for failing to act in good faith during mediation were consistent with the decision rendered by the Panel of Judges. The plaintiff's failure to attend mediation is comparable to failing to attend court, given that mediation is an integral part of the civil trial process. Based on these considerations, the panel of judges decided to dismiss the plaintiff's lawsuit for failing to act in good faith during the mediation process. This decision was made to uphold the principle of good faith in the judicial process and ensure that mediation is not abused by parties who are not serious about resolving the dispute. The recommendation in this study is that the Panel of Judges should enforce the law fairly and issue decisions based on legal facts and available evidence. It is also hoped that the public will be raised awareness about the dangers of embezzlement in office and its impact on organizations and society.